Daily Data is Bad for Beta: Opacity and Frequency-Dependent Betas - Gilbert, Thomas; Hrdlicka, Christopher; Kalodimos, Jonathan; Siegel, Stephan (The Review of Asset Pricing Studies, 2014)
A stock’s market exposure, beta, varies across return frequencies. Sorting stocks on the difference between low- and high-frequency betas (Δβ) yields large systematic mispricings relative to the CAPM at high frequencies, but significantly smaller mispricings at low frequencies. We provide a risk-based explanation for this frequency dependence by introducing uncertainty about the effect of systematic news on firm value (opacity) into a frictionless model. We document a robust relationship between the frequency dependence of betas and proxies for opacity. Our findings suggest that opacity poses significant challenges to using betas estimated from high-frequency returns. While the CAPM may be an appropriate asset pricing model at low frequencies, additional factors, e.g., based on opacity, are necessary at high frequencies. (JEL G11, G12, G13, G14)